2012
DOI: 10.1097/ede.0b013e31824523f0
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Markers of Coagulation, Inflammation, and Endothelial Function

Abstract: BACKGROUND Previous studies suggest that air pollution is related to thrombosis, inflammation, and endothelial dysfunction. Mechanisms and sources of susceptibility are still unclear. One possibility is that these associations can be modified by DNA methylation states. METHODS We conducted a cohort study with repeated measurements of fibrinogen, C-reactive protein, intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) in 704 elderly men participating in the Veterans Admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(161 citation statements)
references
References 38 publications
10
140
1
Order By: Relevance
“…Our findings support previous studies showing an influence of ambient temperature on biomarkers of inflammation 4,5,28 and heart failure, 6 blood viscosity, 7 heart rate variability, 9 blood pressure, 10,11 and cholesterol. 8,12 A correlation between temperature and methylation on repetitive elements has been reported in a previous study focusing on the association of air pollution with LINE-1 and Alu methylation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings support previous studies showing an influence of ambient temperature on biomarkers of inflammation 4,5,28 and heart failure, 6 blood viscosity, 7 heart rate variability, 9 blood pressure, 10,11 and cholesterol. 8,12 A correlation between temperature and methylation on repetitive elements has been reported in a previous study focusing on the association of air pollution with LINE-1 and Alu methylation.…”
Section: Discussionsupporting
confidence: 92%
“…In this cohort, Halonen et al 28 found intermediate-term associations between temperature averaged up to 1 month and C-reactive protein, intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1). Therefore, we focused our analyses on a similar intermediate-term exposure window and considered averages of temperature and relative humidity over 1–3 weeks preceding each participant’s visit.…”
Section: Methodsmentioning
confidence: 74%
“…Therefore, many of the hypothesized mechanisms between air pollution and cardiovascular diseases such as inflammation, oxidative stress, and endothelial dysfunction may also apply to HDP (Brook, 2008). In addition, direct links have been reported between air pollution and endothelial dysfunction, which is regarded as a pre-cursor associated with HDP (Bind et al, 2012; Brook and Rajagopalan, 2012; Steegers et al, 2010). Furthermore, the abnormal placentation and failed vascular remodeling caused by endothelial dysfunction may trigger preeclampsia (Powe et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have also found that exposure to air pollutants such as O 3 is associated with increased platelet aggregation and thrombin generation [24], which are known to lie on the pathway of the pathogenesis of cardiovascular events and stroke. Moreover, a recent study found that exposure to ozone and other air pollutants is predictive of the level of C-reactive protein, which suggests systemic inflammatory responses [25]. These mechanisms suggest that systemic inflammatory and vascular changes following exposure are likely to be responsible for the negative effects of air pollutants on risk of stroke.…”
Section: Discussionmentioning
confidence: 99%